Resveratrol and Omega-3 Fatty Acid: Its Implications in Cardiovascular Diseases - Kakoti, Bibhuti Bhusan; Hernandez-Ontiveros, Diana G.; Kataki, Manjir Sarma; Shah, Kajri; Pathak, Yashwant; Panguluri, Siva Kumar (Frontiers in Cardiovascular Medicine, 2015)
The present review aimed at summarizing the major therapeutic roles of resveratrol and omega-3 fatty acids along with their related pathways. This article reviews some of the key studies involving the health benefits of resveratrol and omega 3 fatty acids. Oxidative stress has been considered as one of the most important pathophysiological factor associated with various cardiovascular disease conditions. Resveratrol with the potent antioxidant and free radical scavenging properties has been proven to be a significantly protective compound in restoring the normal cardiac health. A plethora of research also demonstrated the reduction of the risk of coronary heart disease, hypertension and stroke, and their complications by omega-3 fatty acids derived from fish and fish oils. This review describes the potential cardioprotective role of resveratrol and omega 3 fatty acids in ameliorating the endoplasmic reticulum (ER) stress.